2011
DOI: 10.1002/dvdy.22653
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome remodeling and differentiation of tetraploid embryos during preimplantation development

Abstract: Although it is known that the tetraploid embryo contributes only to the placenta, the question of why tetraploid embryos differentiate into placenta remains unclear. To study the effect of electrofusion on the development of mouse tetraploid oocytes, mouse two-cell embryos were fused and cultured in vitro in Chatot-Ziomek-Bavister medium. After electrofusion, two chromosome sets from the tetraploid blastomere were individually duplicated before nuclear fusion. At 8-10 hr after electrofusion, each chromosome se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…In mid-blastocyst stages, Oct4-positive cells randomly appear within the ICM, whereas Cdx2-positive cells are localized to the outer surface of the ICM. As we previously reported [20], Oct4 expression from the 2-cell to the morula stage was similar in tetraploid and diploid embryos. Interestingly, we discovered that at the expanded blastocyst stage, Oct4 expression had disappeared in most of the tetraploid-derived embryonic cells, though some embryonic cells at the ICM site did remain Oct4-positive.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In mid-blastocyst stages, Oct4-positive cells randomly appear within the ICM, whereas Cdx2-positive cells are localized to the outer surface of the ICM. As we previously reported [20], Oct4 expression from the 2-cell to the morula stage was similar in tetraploid and diploid embryos. Interestingly, we discovered that at the expanded blastocyst stage, Oct4 expression had disappeared in most of the tetraploid-derived embryonic cells, though some embryonic cells at the ICM site did remain Oct4-positive.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, we discovered that at the expanded blastocyst stage, Oct4 expression had disappeared in most of the tetraploid-derived embryonic cells, though some embryonic cells at the ICM site did remain Oct4-positive. Previously, we reported that 83% of the tetraploid-derived blastocysts had 80 chromosomes, and 17% exhibited mixploidy [20], indicating a close relationship between the numbers of tetraploid-derived blastocysts with Oct4-positive cells and aberrant chromosome numbers. We also demonstrated that the transcription levels of ICM-related genes such as Oct4, Sox2 and Klf4 were 0.1-fold lower in tetraploid-derived blastocysts compared with diploid blastocysts (P<0.05).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For fusion 2-cell stage mammalian embryos, different electrofusion parameters were used [23,40] according to the type of fusion buffer, electrofusion instrument and animal species [38]. In mice, the highest tetraploid blastocyst formation rate (93.0%) of fused embryos was achieved when electrofusion was performed using 20-volt AC and 100-volt DC [41]. In rabbits, tetraploid embryos were obtained with a single pulse of 1.4 kV/ cm for 100 μs and 74.5% of them developed to morula and blastocyst stages, with 72.7% of the morulae/blastocysts being tetraploid [40].…”
Section: Discussionmentioning
confidence: 99%
“…May 2016 | Volume 4 | Issue 5 | Page 268 Park et al (2011) reported that most favourable electrofusion voltages were 100 volts DC pulse and 20 volts alternating current in mouse. Tetraploid embryos were further developed and 2-cell stage tetraploid embryos (93%) were achieved after 16 hours of electrofusion, whereas 4-cell stage tetraploid embryos (80%) were achieved after 24 hours.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%